Pasture feeding of lambs with and without supplements in the conditions of Lapland - Liisa Syrjälä (Agricultural and Food Science, 1981)
The need for feeding supplements to lambs on pasture was studied in 1977—1979 in northern Lapland at 69° 40’ N and 27° 05’E, where the pasture period lasts from mid June to mid September. Lambs fed on pasture alone were compared with animals whose diet was supplemented with a barley-oats meal mixture (1:1), given at the level of 400—500 g/animal/day, or large-leaved turnip (Teutoburger), offered ad libitum. The age of the lambs at the beginning of the experiments averaged three months. The live-weight gain of the lambs receiving supplemental feeds did not differ significantly (P < 0.1) from that of the lambs on only pasture feeding, though the supplements tended to have a favourable effect during the second part of the pasture period, or at the beginning of August. The slaughter criteria were better, however, for the lambs receiving supplements. Teutoburger turnip proved to be a good and palatable feed for lambs on pasture. Since it gives good yields even in northern Lapland, Teutoburger can be recommened for northerly regions where cereal crops do not ripen. The growth of lambs in Lapland seems to be decreased by mosquitoes and gnats.